The Efficiency Enhancement on the Direct Flow Evacuated Tube Solar Collector Using Water-Based Titanium Oxide Nanofluids - Mahendran, Moorthy; Tanti Zanariah, Shamshir Ali; Shahrani, Anuar; R. A., Bakar (Trans Tech Publications Inc., 2014)
In the present study, the efficiency of an evacuated-tube solar collector was investigated experimentally by using water and water-based titanium oxide nanofluids as the working fluids. The titanium oxide nanofluids with the average nanoparticles size between 30-50nm were prepared and tested at volume concentration of 1.0%, 2.0% and 3.0%. The volume flow rate of the working fluids in the solar collector varied from 2.0 to 3.0 liter/min. The experiments were performed at outdoor conditions according to the ASHRAE standard 93-2000. The result shows the efficiency of evacuated solar collector have increased up to 42.5% by using 2.0% concentration nanofluids compared to its base fluid at 2.0litre/min flow rate. In conclusion, the efficiency of collector shows greater enhancement at the low volume flow rate and concentration of nanofluids compared to its base fluid which was water.